Diffusion of Innovation Theory Utilization Online Financial Transaction: Literature Review - Syahadiyanti, Litafira; Subriadi, Apol Pribadi (International Journal of Economics and Financial Issues, 2018)
Payment system is a system related to the transfer of the amount of money from one part to anotherpart. The use of online financial transactions is the implementation of technology in the paymentsystem to be faster, precise and accurate. In fact, online transaction very rarely used by the society.This review was required to analyze existing studies on the adoption of online financialtransactions. Based on the literature review conducted, there were several studies that state that notall variables included in the diffusion of innovation theory in accord with the conditions. Only afew variables were suitable for the adoption of online financial transactions at this time. There werethree conceptual models that can be considered from the results of a literature review. Thisliterature review is provided new research opportunities to prove the conceptual model of onlinefinancial transactions adoption reviewed in this paper. Keywords: Adoption, Online Financial Transaction, Diffusion of Innovation Theory JEL Classifications: G4,O3,P2